2018
DOI: 10.1016/j.jaad.2017.12.050
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic manifestations of solid organ transplantation–associated graft-versus-host disease: A systematic review

Abstract: GVHD is a potentially fatal condition that can occur after SOT and often presents with a skin rash. We recommend that dermatologists have a low threshold to consider and pursue this diagnosis in the setting of post-SOT skin eruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 59 publications
1
23
0
1
Order By: Relevance
“…While the presence of donor lymphocytes in the skin does not in itself confirm GVHD, the location of these donor lymphocytes at the dermal‐epidermal junction and exocytosis within the epidermis close to the satellite cell necrosis were interpreted as being supportive of a diagnosis of GVHD. While PCR‐based chimerism studies were helpful in each case tested in this series, the imperfect sensitivity of this assay may lead to falsely negative test results in some instances . Although FISH and chimerism studies are labor‐intensive and therefore have delayed turn‐around time, our study revealed them to be a specific means of diagnosing GVHD, not only for orthotopic liver transplant patients, but also for recipients of other solid organs, such as bilateral lung transplant.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…While the presence of donor lymphocytes in the skin does not in itself confirm GVHD, the location of these donor lymphocytes at the dermal‐epidermal junction and exocytosis within the epidermis close to the satellite cell necrosis were interpreted as being supportive of a diagnosis of GVHD. While PCR‐based chimerism studies were helpful in each case tested in this series, the imperfect sensitivity of this assay may lead to falsely negative test results in some instances . Although FISH and chimerism studies are labor‐intensive and therefore have delayed turn‐around time, our study revealed them to be a specific means of diagnosing GVHD, not only for orthotopic liver transplant patients, but also for recipients of other solid organs, such as bilateral lung transplant.…”
Section: Discussionmentioning
confidence: 82%
“…While PCR-based chimerism studies were helpful in each case tested in this series, the imperfect sensitivity of this assay may lead to falsely negative test results in some instances. 4 Although FISH and chimerism studies are labor-intensive and therefore have delayed turn-around time, our study revealed them to be a specific means of diagnosing GVHD, not only for orthotopic liver transplant patients, but also for recipients of other solid organs, such as bilateral lung transplant. Given the high mortality rate observed in the present cohort of patients, we were unable to determine effective treatment options for SOT GVHD.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations